Aldosterone in chronic kidney disease and renal outcomes . (1st August 2022) - Verma, Ashish; Vaidya, Anand; Subudhi, Sonu; Waikar, Sushrut S
Abstract: Aims: Randomized controlled trials have demonstrated the efficacy of mineralocorticoid receptor (MR) antagonism in delaying chronic kidney disease (CKD) progression in diabetes; however, they have not investigated the role of aldosterone or whether these beneficial effects could be achieved in individuals without diabetes. Methods and results: The association between serum aldosterone concentrations and kidney disease progression was investigated among 3680 participants in the Chronic Renal Insufficiency Cohort. The primary outcome was CKD progression [defined as the composite of 50% decline in estimated glomerular filtration rate (eGFR) or end-stage kidney disease, whichever occurred first]. The associations between serum aldosterone and kidney disease outcomes were assessed using Cox proportional hazard models. At baseline, higher aldosterone concentrations were associated with a lower eGFR, lower serum potassium, greater urinary potassium, and protein excretion. Over a median follow-up of 9.6 years, 1412 participants developed CKD progression. In adjusted models, each doubling of serum aldosterone was associated with a 11% increased risk of CKD progression [hazard ratio (HR) 1.11, 95% confidence interval (CI) 1.04–1.18]. Individuals with the highest quartile of serum aldosterone had a 45% increased risk of CKD progression (HR 1.45, 95% CI 1.22–1.73) compared with the lowest quartile. The risk for CKD progression was similar regardless of whether patients had concomitant diabetes ( P -interaction = 0.10). Conclusion: Higher serum aldosterone levels among individuals with CKD are independently associated with an increased risk for kidney disease progression, irrespective of concomitant diabetes. These findings provide mechanistic support for MR antagonists in delaying CKD progression and suggest that they may also have a role in those without diabetes. Structured Graphical Abstract: Structured Graphical Abstract Aldosterone in chronic kidney disease and renal outcomes: study design and summary results. CI, confidence interval; CKD, chronic kidney disease; eGFR, estimated glomerular filtration rate; ESKD, end-stage kidney disease; HR, hazard ratio; MR, mineralocorticoid receptor.